Scheduling of undergraduate thesis examination: A case study in Industrial Engineering Department of Universitas Sebelas Maret - Cucuk Nur Rosyidi; Endah Budiningsih; Wakhid Ahmad Jauhari (Journal of Industrial Engineering International, 2019)
Undergraduate thesis examination in Industrial Engineering Department of Universitas Sebelas Maret conducted through two stages, namely intermediate and final examination. Currently, the scheduling process of such examinations is done by the undergraduate thesis coordinator manually without certain systematic method or approach. In this paper, we develop an optimization model for the examinations scheduling considering several factors, namely the number of lecturers that must attend the examinations, the availability of rooms for examinations, the availability of each lecturer, and the assignment distributions. The model uses integer programming approach. Two performance criteria are used in the model, namely the difference between the number of each lecturer's assignment with the average number of lecturer assignments and the number of penalties from the assignment of lecturers on certain time slot. The developed model is able to solve the scheduling problem more efficiently than manual scheduling done by thesis coordinator. The optimal solutions from the optimization model show a total difference in the assignment of lecturer with an average of 29.6 and a penalty of 0.
Keywords: 650; Scheduling; Timetabling; Integer programming; Invigilator assignment